FootSense: An AI-Augmented Foot-Tactile System for Emotion and Social Regulation in Pervasive Health Contexts - Shi, Zhulin; Zhou, Hao; Chen, Liuqing; Chen, Yao; Huang, Guanghui; Ying, Weiqiang (EAI Endorsed Transactions on Pervasive Health and Technology, 2026)
INTRODUCTION: FootSense proposes a novel approach to emotional and social regulation through foot-tactile feedback in public spaces. Unlike conventional upper-body haptic systems, it utilizes the feet as a discreet, low-interference interface. By integrating rhythmic, directional, and social-cue tactile stimulation, FootSense modulates emotional states and enhances social interactions in dynamic environments.OBJECTIVES: This study aims to develop and validate a multi-mechanism foot-tactile model that facilitates emotional relief and social approach in real-world public settings.METHODS: We developed FootSense, an AI-augmented ambient intelligence system combining behavioral sensing, contextual inference, and adaptive tactile feedback. A two-week field experiment (N=200, five groups) was conducted across four public environments—mall, campus, hospital, and transit hub—to compare rhythmic, directional, and fusion tactile modes. Data were analyzed via ANOVA, mixed-effects modeling, and correlation analysis.RESULTS: Rhythmic feedback reduced state anxiety (ΔSAI = –7.5, p
Keywords: foot-tactile interaction; AI-augmented ambient intelligence; emotional regulation; social approach behavior; multi-mechanism model; wearable haptic system; digital health intervention